2017
DOI: 10.2174/1874431101711010001
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Competence on Physiologic Monitors Use: Toward Eliminating Alarm Fatigue in Intensive Care Units

Abstract: Background:Studies on nurse competence on alarm management are a few and tend to be focused on limited skills. In response to Phase II of implementing the National Patient Safety Goal on clinical alarm systems safety, this study assessed nurses’ perceived competence on physiologic monitors use in intensive care units (ICUs) and developed and validated a tool for this purpose.Methods:This descriptive study took place in a Magnet hospital in a Southwestern state of the U.S. A Nurse Competence on Philips Physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Nurses are the primary users and maintainers of monitors (Ruppel et al., 2019); thus, their alarm management behaviour is key in determining the occurrence of nonactionable alarms and alarm fatigue. According to a previous study, 3%–40% of healthcare workers indicated they had never used many of the monitoring functions of a monitor (Sowan et al., 2017). In recent years, the Emergency Care Research Institute reported 216 deaths resulting from improper alarm management (Keller, 2012), and they listed alarm‐related issues as the most important factors affecting the safety of patients in consecutive years (Cvach, 2012; Ruppel, Funk, Clark, et al, 2018; Ruppel, Funk, Kennedy, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are the primary users and maintainers of monitors (Ruppel et al., 2019); thus, their alarm management behaviour is key in determining the occurrence of nonactionable alarms and alarm fatigue. According to a previous study, 3%–40% of healthcare workers indicated they had never used many of the monitoring functions of a monitor (Sowan et al., 2017). In recent years, the Emergency Care Research Institute reported 216 deaths resulting from improper alarm management (Keller, 2012), and they listed alarm‐related issues as the most important factors affecting the safety of patients in consecutive years (Cvach, 2012; Ruppel, Funk, Clark, et al, 2018; Ruppel, Funk, Kennedy, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…5,8,[13][14][15] A recent study demonstrated a lack of nurse competence on physiological monitor use, emphasising the need for further monitor education and training for nurses. 16 Additional knowledge and understanding of how nurses use monitors and how nuisance alarms can be decreased to enhance patient safety and quality of care is needed. With these considerations, the aim of this study was to explore both how nurses use monitors in patient surveillance within coronary care and the impact that monitors have on nurses' work.…”
Section: Introductionmentioning
confidence: 99%
“…Nearby 566 records of patient dooms related to screening apparatus alarms during 2005-2008 obtained through the FDA Administration. In additional definite pattern, the FDA 2010 received more than 2500 adverse incident determination connected with mechanical ventilator utilize, wherein one third of the episodes indicated an alarm fatigue linked topics (Bach, Berglund, & Turk, 2018, Sowan et al, 2017. This information is recommended to be an underestimation of an overlooked patient safety issue.…”
Section: Introductionmentioning
confidence: 99%